Deletion of TRPC6 Attenuates NMDA Receptor-Mediated Ca2+ Entry and Ca2+-Induced Neurotoxicity Following Cerebral Ischemia and Oxygen-Glucose Deprivation - Chen, Jin; Li, Zhaozhong; Hatcher, Jeffery T.; Chen, Qing-Hui; Chen, Li; Wurster, Robert D.; Chan, Sic L.; Cheng, Zixi (Frontiers in Neuroscience, 2017)
Transient receptor potential canonical 6 (TRPC6) channels are permeable to Na+ and Ca2+ and are widely expressed in the brain. In this study, we investigated the role of TRPC6 following ischemia/reperfusion (I/R) and oxygen-glucose deprivation (OGD). We found that TRPC6 expression was increased in wild type (WT) mice cortical neurons following I/R and in primary neurons with OGD, and that deletion of TRPC6 reduced the I/R-induced brain infarct in mice and the OGD- /neurotoxin-induced neuronal death. Using live-cell imaging to examine intracellular Ca2+ levels ([Ca2+]i), we found that OGD induced a significant higher increase in glutamate-evoked Ca2+ influx compared to untreated control and such an increase was reduced by TRPC6 deletion. Enhancement of TRPC6 expression using AdCMV-TRPC6-GFP infection in WT neurons increased [Ca2+]i in response to glutamate application compared to AdCMV-GFP control. Inhibition of N-methyl-d-aspartic acid receptor (NMDAR) with MK801 decreased TRPC6-dependent increase of [Ca2+]i, indicating that such a Ca2+ influx was NMDAR dependent. Furthermore, TRPC6-dependent Ca2+ influx was blunted by blockade of Na+ entry. Finally, OGD-enhanced Ca2+ influx was reduced, but not completely blocked, in the presence of voltage-dependent Na+ channel blocker tetrodotoxin (TTX) and dl-α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid (AMPA) blocker CNQX. Altogether, we concluded that I/R-induced brain damage was, in part, due to upregulation of TRPC6 in cortical neurons. Overexpression of TRPC6 following I/R may induce neuronal death partially through TRPC6-dependent Na+ entry which activated NMDAR, thus leading to a damaging Ca2+ overload. These findings may provide a potential target for future intervention in stroke-induced brain damage.